SELF-ESTEEM, EMOTIONAL INTELLIGENCE AND ACADEMIC PERFORMANCE AMONG COLLEGE STUDENTS IN A SELECTED COLLEGE, MURSHIDABAD - Pal, Puja; Choudhuri, Moitreyee (International Journal of Research -GRANTHAALAYAH, 2024)
Introduction: Self-esteem refers to the degree of consideration or respect that people have for themselves and emotional intelligence is the ability to understand, perceive, express and regulate one’s emotions. Students are future pillars of our society. Self-esteem and emotional intelligence may act as a anticipator of academic performance of students. Aim: This study aims to find out the relationship between self-esteem, emotional intelligence and academic performance among college students. Method: The investigator conducted a descriptive survey on self-esteem, emotional intelligence and academic performance among college students in a selected college Murshidabad. The population of the study was all college students. By using stratified random sampling techniques 150 students were selected. Strata was made as per year on which, students were study Bachelor of Art (pass course) degree programme, from selected College, Murshidabad. Socio demographic data were collected by using semi-structured questionnaire. Standardized validated and reliable tools (Rosenberg self-esteem scale, Schutte Self Report Emotional Intelligence Test and Academic Performance scale) were used to collect data. Result: The study result revealed that 29.33 % college students had high level of self-esteem, 70% had average self-esteem and 0.67% had low self-esteem. Most of the students (26.67 %) need to develop emotional intelligence and 15.33 % students had significant strength in their emotional intelligence level. It showed that 37.33 % college students had performed good in their academic area and 2% had failed academic performance. It also revealed a positive correlation (‘r’ = 0.54) between self-esteem and emotional intelligence which is statistically significant (‘t’ = 7.80; df (149) and p<0.05). This study also showed a positive correlation (‘r’ = 0.48) between self-esteem and academic performance of college students which is statistically significant (‘t’ = 6.65; df(149) and p<0.05). There was highly positive correlation (‘r’ = 0.74) among college students’ emotional intelligence and academic performance which is statistically significant (‘t’ = 13.03; df (149) and p<0.05). The study had implication on Nursing practice, administration, education